THE EFFECT OF PRICE, SERVICE AND PROMOTION ON REPURCHASE DECISION OF WATER REFILLS PRODUCT OF METRO PALU - Nurmiati, Nurmiati; Miru, Sulaeman; Santi, Ira Nuriya (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2022)
This research aims to determine and analyze the effect of price, service, and promotion simultaneously and partially on decision to repurchase the product of water refills of Metro Palu. The population in this research were all customers of the Metro Palu refill water refills station. The number of samples in this research were 123 respondents. This research applied a descriptive causal with data analysis technique using multiple linear regression. Data were analyzed through SPSS application. The results show that the variables of price, service and promotion simultaneously have a positive effect on repurchase decisions, the significant value of F is 0.000 < (0.05). Moreover, the partial test result obtains that the price variable has a significant value of t = 0.006 < (0.05). It can be concluded that the price variable positively and significantly affects on repurchase decision. Furthermore, the service variable has a significant value of t = 0.006 < (0.05) so it can be concluded that the service variable has a positive and significant effect on repurchase decision. The results of the partial test show that the promotion variable has a significant value of t = 0.000 < (0.05). Thus, so it can be concluded that the promotion variable has a positive and significant effect on repurchase decision. Keywords: Prices, Services, Promotions, Repurchase Decisions, Metro Palu Water Refills